PENINGKATAN KEMAMPUAN WIRAUSAHA MELALUI PENDIDIKAN JAHIT DAN BORDIR PADA PANTI ASUHAN AL-HUSNA DI LANDUNGSARI KECAMATAN DAU KABUPATEN MALANG (UPGRADES ENTREPRENEURSHIP THROUGH EDUCATION SEWING AND EMBROIDERY AT ORPHANAGE AL-HUSNA IN LANDUNGSARI SUBDISTRICT DAU MALANG) - Soelistyo, Aris (Studi Kasus Inovasi Ekonomi, 2016)
The Qur'an insists on the importance of care for orphans, thepoor and helping others in various fields. Orphanage AlHusna Malang, the vision and mission based on concern forthe orphans and the poor. A number of programs to helporphans, orphans and dhu'afa. The program was conducted onthe educational, social and religious. Al-Husna FoundationProgram includes six courses that regular donors program,the movement of the foster parents' caring school ", theprogram waqaf" RIDHA "(orphanages and orphans alHusna), independent nursing program, Barbepa (thriftrewarding) and program TABASAM (Savings dear orphans).One effort to educate and improve the ability of residentswere largely children of school age, including the ability ofmastering techniques of sewing and embroidery techniques.Of both skill capabilities will deliver on independententrepreneurship in the perspective of the future (as abusiness opportunity) in realizing the independent nursingprogram. The community service approach or method oflecture and hands-on ability to sew in children orphanage aswell as the ability to create design patterns clothes Resultsshowed that the strong enthusiasm of the children orphanageAl-Husna Dau to gain additional expertise in the field ofsewing and to develop or establish a pattern design clothes.